Czwarta władza – media a ład prawny demokratycznego społeczeństwa - Torczyńska, Monika (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
It is far from controversial to state that the media the ‘fourth power’ in the reality of a contemporary democratic state. The media play key role in the implementation of the legal order ensuring every subject an inalienable right to obtain and spread information. The current position of the media is a result of more than just being an intermediary in the social circulation of the news which is relevant for the members of a given community. Ass media able to create a new political, legal or business establishment. On behalf of the society itso exerts prssure on state authorities in order to enforce desirable legal and political decisions (e.g. the amendments of law). This leads to the following statement: “Liberal doctrine attaches such a great importance to the role of the media as the watchdog of democracy that it assigns it w the status of the fourth power in the state”.